ANALISIS USER EXPERIENCE MAHASISWA TERHADAP SISTEM INFORMASI SIASAT MENGGUNAKAN USER EXPERIENCE QUESTIONNAIRE - Eirene Claudia Ratmoko; Magdalena Ariance Ineke Pakereng (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
The current development of information systems needs to be reviewed whether the quality of the information system is able to answer the needs of its users. One of the information system technologies is the Satya Wacana Academic Information System (SIASAT), which until now there has been no research that discusses the level of user experience satisfaction when using the SIASAT. Therefore, an analysis of the student SIASAT user experience was carried out using the User Experience Questionnaire (UEQ) method. UEQ is a measurement measured from aspects of its use and aspects of experience including compressive impressions with a questionnaire scale. UEQ has 26 questions covering 6 scales, including the attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty scales. The final result of the study concluded that for the attractiveness scale, the evaluation value was normal and the benchmark was Bad. The perspicuity scale gets a positive evaluation value and the benchmark is Above Average. The efficiency scale gets a normal evaluation value and a Bad benchmark. The dependability scale gets normal evaluation values and Bad benchmark. The stimulation scale gets a normal evaluation value and a Bad benchmark. The novelty scale gets a negative evaluation score and the benchmark is Bad.